Development of E-Worksheet Problem-Based Learning Model with Ethnoscience Content to Improve Critical Thinking Skills - Setyawati, Annisa; Prasetya, Agung Tri (Chemistry in Education, 2025)
This study was designed as an E-worksheet model of Problem-Based Learning with ethnoscience content. The study aimed to produce a product, analyze its feasibility and effectiveness in improving students' critical thinking skills. The study included research and development (R&D) with a 3D (Three-D) design consisting of the Define, Design, and Develop stages. The research model is a quasi-experimental design using a posttest-only control group design. The study subjects consisted of 71 students from grades XI-11 and XI-12. Data collection methods included both test and non-test instruments. Data collection instruments included interview sheets, questionnaires, surveys, and assessments. Data analysis of the developed product included feasibility tests, effectiveness tests, and student responses to the E-worksheet product. The research results showed that the expert validation of the material, media, and readability test indicated that the E-worksheet product was feasible for use, with Aiken's V coefficients of 0.95 and 0.89, which are very high criteria, and a score percentage of 87.06%, which is a very good criterion. The results of the large-scale trial showed that the E-worksheet was effective in improving critical thinking skills based on the Mann Whitney test result of 0.002 < 0.05, which indicated a significant difference in critical thinking skills between the experimental class and the control class. The E-worksheet product received a very good response from students with a score of 90.48%. The E-worksheet PBL model with ethnoscience content developed is feasible and effective in improving critical thinking skills and receives a very good response from students.